(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Inadequate documentation and information of Non-Timber Forest Products (NTFPs) in the study sites call for the assessment of composition and diversity of the concern products. Therefore, the aim of the study is to assess the Composition and Diversity of Non- Timber Forest Products (NTFPs) in Baturiya Wetland Game Reserve, Jigawa State, Nigeria. A four (4) transects of 1km length was laid at an interval of 400 m. Likewise, in each transect, 4 plots of 100 x 100 m was laid alternately along each transect at 200 m interval. Also four (4) quadrants of 1m x1m in size for small non-timber forest products was randomly laid in each 100 x100m plot for each of the habitats in each plot, plant stocks identified were recorded. Data collected were analysed using Simpson index, Sorenson index and descriptive statistic. Results showed that Upland area had the highest species, number of individual and diversity of Non–Timber Forest Product followed by Swampy area and Fadama area with the values of (94, 1464, D-0.981), (63, 842, D-0.970) and (60, 805, D-0.969) respectively. Upland area and Swampy area had the highest similarity index of 78.5%. The results suggest that the documentation, inventory and management of NTFPs should be addressed in operational plan to enhance its diversity